1977
DOI: 10.1159/000198066
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Increased Amylase to Creatinine Clearance Ratio in Acute Pancreatitis

Abstract: The amylase to creatinine clearance ratio was found to be normal in 11 of 33 patients with acute pancreatitis. The ratio was elevated in 10 of 19 patients with renal insufficiency. Thus, it does not seem to be a specific index in the diagnosis of acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In patients with pancreatitis this ratio is increased and may exceed 10%. Although an increased ACCR was thought to be helpful for the diagnosis, it has been shown to have little value because of its low specificity [19][20][21][22][23].…”
Section: Urinary a Mylasementioning
confidence: 99%
“…In patients with pancreatitis this ratio is increased and may exceed 10%. Although an increased ACCR was thought to be helpful for the diagnosis, it has been shown to have little value because of its low specificity [19][20][21][22][23].…”
Section: Urinary a Mylasementioning
confidence: 99%
“…While some confirmed the value of this investigation (2 -5 ), others demonstrated that a normal CAm/CCr does not exclude acute pancreatitis (6 -8 ) as has been previously sug gested (9). Furthermore, other groups question the specificity of the CAm/Ccr> reporting raised values in several conditions other than pancre atitis: bums and ketoacidosis (10), acute duo denal perforation (11), renal insufficiency (6,8,(12)(13)(14) and thoracic operation (15,16).…”
Section: Warshaw and Fullermentioning
confidence: 99%
“…They postulated that the Cam/Ccr ra tio may be a useful tool to distinguish hyperamylasemia due to pancreatitis from that caused by other diseases. The diagnostic value of this test has not been confirmed by other groups [6,7], 1.1.4. Isoamylase Isoamylase determination in serum, urine, and other body fluids potentially in creases the specificity of the conventional amylase test.…”
Section: Urine Amylasementioning
confidence: 67%